The cat in the hat comes back! - Seuss, Dr. ([New York] Beginner Books, 1958)
That behatted and bow-tied cat from Dr. Seuss's The Cat in the Hat is back, and, not surprisingly, is up to all sorts of mischief. This time, Sally and her brother are stuck shoveling snow: "This was no time for play./ This was no time for fun./ This was no time for games./ There was work to be done." But--you guessed it--the laughing Hat Cat has other ideas, as he lets himself in to eat cake in their tub. He leaves behind "a big long pink cat ring," which he then handily cleans with "MOTHER'S WHITE DRESS!" The dress then loses its pink stain to the wall, then Dad's shoes, then the rug in the hall, until finally the Cat must call in some assistance: from inside his hat comes Little Cat A, then Littler Cats B, C, D, E, and so on, nested like dolls in ever tinier hats. With this pack of felines, Sally and her brother may get rid of those stains, but they'll likely never be rid of that rascally cat. As should be expected from the good doctor, The Cat in the Hat Comes Back provides an excellent reader (and alphabet primer) for those just learning, not to mention ample laughs for everyone else. (Ages 4 to 8) --Paul Hughes
Keywords: Beginner Books